Phenotypic features of dendritic cells when using different modes of their stimulated maturation - F. A. Fadeyev; A. D. Aleksandrova; A. S. Mogilenskikh (Медицинская иммунология)
Monocyte-derived dendritic cells (DCs) can be used for cell immunotherapy of cancer. In most cases, mature DCs, loaded with tumor-associated antigens, are used for immune therapy. The functionality of DCs for immunotherapy substantially depends on their immunophenotype and secretory profile, which are established after DCs maturation. The purpose of this research was to explore the phenotype of DCs after using various approaches for stimulation of their maturation.Maturation of DCs was stimulated by pro-inflammatory cytokines and their mixtures, or by ligands to the TLRs of DCs. DCs were stimulated by the following means: TNF; poly I:C; LPS; cytokine cocktail (TNF + IL-1 + IL-6 + PGE2); the cocktail mixed with poly I:C; and melanoma cells lysate. Forty-eight hours after stimulation, the expression of DCs’ receptors involved into their interaction with T cells, was evaluated by flow cytometry. Moreover, the secretion of IL-12 (activator of T cell response) and IL-10 (inhibitor of T cell response) was estimated by ELISA technique.We have shown that, following stimulation with cytokine cocktail, the DCs exhibit highest expression of receptors, which are necessary for interaction with T cells and for activation of T cell mediated immune response, i.e., antigen-presenting receptors (HLA-DR), co-stimulatory receptors (CD83, CD40, CD86), and receptors controlling the migration of DCs to lymph nodes (CCR7). Moreover, the cocktail-stimulated DCs intensively secrete both IL-12 and IL-10. The stimulatory effect of TNF and poly I:C proved to be moderate: the expression of most receptors was significantly lower than after using the cocktail; no significant differences from control (in absence of induced maturation) in IL-12 secretion were detected. LPS and melanoma cell lysate did not affect both expression of receptors and secretory profile of DCs. Addition of poly I:C to the cytokine cocktail did not affect the receptor expression, but significantly increased the secretion of both proinflammatory IL-12 and anti-inflammatory IL-10.The results of experiments demonstrate that the mixture of cytokine cocktail and poly I:C seems to be the most effective tool for stimulation of DCs maturation. However, further experiments are required to compare the functionality of DCs when using different tools for induced DC maturation.